Ivan Petrovich Pavlov and Santiago Ramón y Cajal, scientists and Nobel laureates of a new century - Jairo Alonso Rozo; Leonardo Palacios-Sánchez; Andrés Manuel Pérez-Acosta (Arquivos de Neuro-Psiquiatria, 2022)
ABSTRACT Pavlov and Cajal were two influential scientists who developed their work in the late nineteenth and early twentieth centuries. Both won the Nobel Prize in Physiology or Medicine. The authors analyze the similarities between their life and work, delving into a single aspect: the Nobel prize obtained by both with only two years of difference: Pavlov in 1904 and Cajal in 1906, shared with Camilo Golgi. Both belonged to two declining empires when nationalism was still of some importance. The theories proposed by them more than 115 years ago are still valid in much of what they contributed in their respective disciplines.